Anti‐HIV‐1 antibodies trigger non‐lytic complement deposition on infected cells. (12th December 2019) - Dufloo, Jérémy; Guivel‐Benhassine, Florence; Buchrieser, Julian; Lorin, Valérie; Grzelak, Ludivine; Dupouy, Emilie; Mestrallet, Guillaume; Bourdic, Katia; Lambotte, Olivier; Mouquet, Hugo; Bruel, Timothée; Schwartz, Olivier
Abstract: The effect of anti‐HIV‐1 antibodies on complement activation at the surface of infected cells remains partly understood. Here, we show that a subset of anti‐Envelope (Env) broadly neutralizing antibodies (bNAbs), targeting the CD4 binding site and the V3 loop, triggers C3 deposition and complement‐dependent cytotoxicity (CDC) on Raji cells engineered to express high surface levels of HIV‐1 Env. Primary CD4 T cells infected with laboratory‐adapted or primary HIV‐1 strains and treated with bNAbs are susceptible to C3 deposition but not to rapid CDC. The cellular protein CD59 and viral proteins Vpu and Nef protect infected cells from CDC mediated by bNAbs or by polyclonal IgGs from HIV‐positive individuals. However, complement deposition accelerates the disappearance of infected cells within a few days of culture. Altogether, our results uncover the contribution of complement to the antiviral activity of anti‐HIV‐1 bNAbs. Synopsis: Anti‐HIV‐1 antibodies trigger complement deposition at the surface of infected cells. Some viral and cellular components independently limit complement activation after infection, preventing rapid cell lysis, although coated cells disappear faster than non‐coated cells. Some anti‐HIV‐1 bNAbs and polyclonal antibodies trigger complement deposition on infected cells. Infected primary CD4 T cells resist complement lysis by bNAbs. Vpu, Nef and CD59 cooperate to limit complement activation by antibodies. Abstract : Anti‐HIV‐1 antibodies trigger complement deposition at the surface of infected cells. Some viral and cellular components independently limit complement activation after infection, preventing rapid cell lysis, although coated cells disappear faster than non‐coated cells.